REKAYASA BRACING TIPE V DAN TIPE Î› PADA GEDUNG KAMPUS - Dwi Kurniati (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
Bracing is a reinforcement of reinforced concrete structures so that the main components can work optimally and become one unit when receiving earthquake loads. Bracing has been widely applied as an effort to strengthen the building structure. Bracing also consists of various elements ranging from reinforced concrete, steel, and others. The object of research is a 6-story campus building located in the Babarsari area of Yogyakarta. This campus building is considered vulnerable because the distance from the Opak fault is only approximately 6 km, not only that the campus building is also not far from the Mataram Ditch with a distance of about 1 km. This ditch stretches from north to south Yogyakarta. The purpose of this study was to determine the value of the deviation between the use of type V and Î› bracing in the campus building. The method used in this engineering refers to the regulations of SNI 1726:2019 â€œTata Cara Perencanaan Ketahanan Gempa untuk Bangunan Gedung dan Non Gedungâ€, SNI 1727:2020 â€œBeban Minimum Untuk Perancangan Gedung dan Struktur Lainâ€, and SNI 2847:2019 â€œPersyaratan Beton Struktural Untuk bangunan Gedungâ€, The analysis was carried out with the help of ETABS V.19 software. The results obtained are the value of the decrease in deviation between floors in the X and Y axes. The average value of the type V bracing deviation is 5.40 in the X direction and 5.63 in the Y direction, and the average value of the type Î› bracing deviation is 39.27 in the X direction and 24.23 in the direction Y, so if an earthquake occurs in the campus building, it will reduce structural damage, so that the building can be said to be safe.